Alamandine reverses hyperhomocysteinemia‐induced vascular dysfunction via PKA‐dependent mechanisms. Issue 6 (4th October 2017) - Qaradakhi, Tawar; Matsoukas, Minos Timotheos; Hayes, Alan; Rybalka, Emma; Caprnda, Martin; Rimarova, Kvetoslava; Sepsi, Milan; Büsselberg, Dietrich; Kruzliak, Peter; Matsoukas, John; Apostolopoulos, Vasso; Zulli, Anthony
Summary: Introduction: Hyperhomocysteinemia (HHcy) impairs nitric oxide endothelium‐dependent vasodilation, consequently leading to atherosclerosis, a risk factor for cardiovascular disease. Novel treatments for HHcy are necessary. Aim: We tested the hypothesis that alamandine, a vasoactive peptide of the renin‐angiotensin system (RAS), could reverse HHcy‐induced vascular dysfunction through the MrgD receptor and that this is mediated by the protein kinase A (PKA) pathway. Furthermore, we sought to determine a putative binding model of alamandine to the MrgD receptor through docking and molecular dynamics simulations. Method: The abdominal aorta was excised from New Zealand white rabbits (n = 15) and incubated with 3 mmol/L Hcy (to mimic HHcy) to induce vascular dysfunction in vitro. Vascular function was assessed by vasodilatory responses to cumulative doses of acetylcholine. Result: Vasodilation was significantly impaired in HHcy‐incubated aortic rings while alamandine reversed this effect (control, 74.2 ± 5.0%; Hcy, 30.3 ± 9.8%; alamandine + Hcy, 59.7 ± 4.8%, P < .0001). KT5720 (PKA inhibitor) significantly inhibited the ability of alamandine to attenuate the impaired vasodilation caused by HHcy (KT5720 + Hcy + alamandine, 27.1 ± 24.1, P < .01). Following immunohistochemistry analysis, the MrgD receptor was highly expressed within the media and endothelial layer of aortic rings in HHcy compared to control (media: 0.23 ± 0.003 vs control 0.16 ± 0.01, P < .05 and endothelium: 0.68 ± 0.07 vs control 0.13 ± 0.02, P < .01, in PA/I (A.U) units). Computational studies also propose certain interactions of alamandine within the MrgD transmembrane domain. Conclusion: This study shows that alamandine is effective in reversing HHcy‐induced vascular dysfunction, possibly through the PKA signaling pathway via MrgD. Our results indicate a therapeutic potential of alamandine in reversing the detrimental effects of HHcy.